Prospective Teachers' Learning Strategies in Learning English - Laila Amalia; Jenny Elvinna Manurung (Didascein : Journal of English Education, 2024)
Language learning strategies are specific actions, processes, acts, or methods that students frequently use to improve their language proficiency. Learning strategies are crucial for language learners since they facilitate the learners in processing language learning and acquisition. This current research highlights the investigation of prospective teachers’ preferences on learning strategies they mostly adopt when learning English. This research used a cross-sectional survey design. The sample was 147 prospective teachers, selected by using total sampling. The data was obtained using a Strategy Inventory of Language Learning (SILL) questionnaire, version 7.0., adopted from Oxford (1990) which consisted of 50 items measuring 6 learning strategies: memory, cognitive, compensation, metacognitive, affective, and social. The students used a Likert scale of 5 ratings to respond to each item of the questionnaire describing their preferences and experience in learning English. The obtained data were analyzed descriptively by measuring and comparing the mean score range to identify which learning strategy was mostly employed by the students in English language learning. The research findings showed that the mean score of metacognitive strategy was 3.625. It was higher than other learning strategies. It indicated that the prospective teachers mostly adopted the metacognitive as their learning strategy in learning English.